Analysis of the Nutritional and Organoleptic Content of Mujair Fish (Oreochromis mosammbicus) in Lake Limboto and Popayato Aquaculture Ponds - Dunggio, Noviyanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
ABSTRACTTilapia fish (Oreochromis mosammbicus) is a type of cultivated fish that can live in fresh and brackish water. This fish is a fish that is currently widely cultivated and the production is quite high, has developed quite quickly, is easy to obtain and has a lot of high nutritional content. The purpose of this study was to determine the comparison of the chemical quality of tilapia fish (Oreochromis mosammbicus) in Limboto Lake and Popayato Cultivation Ponds. This type of qualitative descriptive research. Fish samples were obtained from Limboto Lake and Popayato Cultivation Ponds. Tilapia fish samples were tested for organoleptic and chemical quality tests (proximate). The organoleptic test includes appearance, taste, aroma and texture. The chemical quality content includes water content, ash content, fat content and protein content. The results showed that there were differences in the nutritional content of tilapia fish from Limboto Lake and Popayato Cultivation Ponds. Judging from the organoleptic tests on the appearance, taste, aroma and texture of the Limboto tilapia fish, it is different from the tilapia fish originating from the Popayato Cultivation Ponds. The chemical test results for the Limboto tilapia fish obtained a water content of 75.91%, an ash content of 1.06%, a protein content of 18.64%, a fat content of 3.73% and for tilapia fish in Popayato Cultivation Ponds a water content of 77.10 was obtained. %, ash content 1.16%, protein content 17.55% and fat content 3.58%. Keywords: Mujair fish (Oreochromis mosammbicus); Nutrient content ; Organoleptic